Identification, Evaluation, and Prioritization of Transparency Policy Implementation Indicators in Iranian Public Organizations (Case Study: Ministry of Industry, Mine, and Trade) - Hosseinpour, Salar; Mousakhani, Morteza; Daneshfard, Karamallah (Management Strategies and Engineering Sciences, 2023)
This study aimed to identify, evaluate, and prioritize the indicators for assessing the implementation of transparency policies in Iranian public organizations, focusing on the Ministry of Industry, Mine, and Trade. The research employed a sequential mixed-methods design with an exploratory approach. Qualitatively, it included a Delphi method, and quantitatively, it used a descriptive method with survey/correlation phases. The qualitative population comprised theoretical foundations and related literature from domestic and international databases, while the Delphi phase involved 15 experts selected via purposive non-random sampling. In the quantitative phase, the statistical population consisted of all administrative staff of the Ministry of Industry, Mine, and Trade, from which 350 respondents were selected using stratified random sampling. Data collection methods included literature review and worksheets for the Delphi phase in the qualitative section, and a researcher-developed 51-item questionnaire (for internal validity) and a 34-item questionnaire (to assess model validity) in the quantitative section. Validity and reliability were examined across all phases, with results confirming the tools' adequacy. Data analysis methods comprised systematic analysis in the qualitative section, Kendall’s coefficient of concordance in the Delphi phase, and descriptive and inferential statistics (confirmatory factor analysis and one-sample t-test) in the quantitative phase, conducted using Maxqda-V2018, SPSS-V23, and SmartPLS-V3 software. The results revealed that the evaluation of transparency policy implementation in the Ministry of Industry, Mine, and Trade includes dimensions of content evaluation with components of formative factors (8 indicators) and procedural factors (11 indicators); implementation evaluation with components of implementers (6 indicators), regulations and policies (8 indicators), and support (5 indicators); and outcome evaluation with components of social outcomes (7 indicators) and organizational outcomes (6 indicators). Finally, a research model was designed based on these dimensions, components, and indicators, which was validated for internal and external reliability, demonstrating appropriate model validity. The findings underscore the importance and necessity of addressing various dimensions of transparency in policy implementation within Iranian public organizations. By identifying and prioritizing key indicators, this research contributes to improving decision-making processes and enhancing accountability in these organizations. Moreover, the results emphasize that focusing on formative factors, processes, and social and organizational outcomes can lead to the development of a comprehensive and efficient model for evaluating transparency. This model not only aids in enhancing the internal performance of the ministry but also serves as a framework for other public organizations to strengthen transparency and accountability within the administrative system of the country.